Estrategia de capacitación para los recursos humanos empleados en el Almacén Casa Bella, de La Maná, Ecuador - Madril Mora, Diana (2010)
The training process constitutes a technique of indispensable address in the administrative activity in the adaptation toward the change. It is a process inside the Administration of Human resources (GRH) that allows to develop the personnel of the company in function of the execution of the managerial objectives. In the present investigation concepts and focuses of this practice are approached in the DRH, with the objective of proposing a training strategy for the Warehouse marries Beautiful, adjusted to the characteristics of this company….